PERMASALAHAN TIDAK DILAKSANAKANNYA ASAS ITIKAD BAIK DALAM PERJANJIAN ELEKTRONIK - Warno Warno (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
AbstractThat the Republic of Indonesia is including developing countries, and the development of the Indonesian state is not just in one area, but in all fields. In the long term development of this began to seem that the people of Indonesia experienced a change that leads kemasyarakat consumptive and productive. It is very clear from the diverse needs of the community and are included in the category of simple goods to luxury goods.Facts show that gradually and surely. the forms of agreements that are used in Indonesian society has changed and agreement perkembangarn Originally conceived as the terms and conditions agreed by the parties as a result of negotiations or negotiations between parties making. However, at this point indicates that most are not found agreement in the form of standard or standard (standardized contract) and electronic agreement (digital contract) are widely used in electronic commerce (e-commerce).The need for cadre for law enforcement to recognize and further insight and depth of technology and electronic information in order to avoid mistakes in the understanding of technology and electronic information that, due to the implementation of the legal acts that occurred conventional system differs from the implementation of the legal actions that have used technology systems